2018
DOI: 10.1039/c7ra11869d
|View full text |Cite
|
Sign up to set email alerts
|

Packed hybrid silica nanoparticles as sorbents with thermo-switchable surface chemistry and pore size for fast extraction of environmental pollutants

Abstract: Thermoresponsive poly(N-isopropylacrylamide)-grafted silica nanoparticles were synthesized and used to prepare solid phase extraction sorbents with switchable pore size and surface chemistry for temperature-regulated extraction of water pollutants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Figure A shows the ATR-FTIR spectra of the native and immobilized enzyme. The silica particles display a broad peak at 1070 cm –1 , resulting from asymmetric vibrations of Si–O . The enzyme immobilization results in new peaks, particularly the amide I band (1600–1700 cm –1 ) related to C–O stretching vibrations and the amide II band (1510–1580 cm –1 ) related to N–H bending. , New peaks between 3000 and 3700 cm –1 are indicative of N–H stretching and side-chain stretching. , In addition, zeta potential measurements reveal surface charge inversion, confirming the successful deposition of layers (Figure B).…”
Section: Results and Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Figure A shows the ATR-FTIR spectra of the native and immobilized enzyme. The silica particles display a broad peak at 1070 cm –1 , resulting from asymmetric vibrations of Si–O . The enzyme immobilization results in new peaks, particularly the amide I band (1600–1700 cm –1 ) related to C–O stretching vibrations and the amide II band (1510–1580 cm –1 ) related to N–H bending. , New peaks between 3000 and 3700 cm –1 are indicative of N–H stretching and side-chain stretching. , In addition, zeta potential measurements reveal surface charge inversion, confirming the successful deposition of layers (Figure B).…”
Section: Results and Discussionmentioning
confidence: 81%
“…The silica particles display a broad peak at 1070 cm −1 , resulting from asymmetric vibrations of Si−O. 50 The enzyme immobilization results in new peaks, particularly the amide I band (1600−1700 cm −1 ) related to C−O stretching vibrations and the amide II band (1510−1580 cm −1 ) related to N−H bending. 51,52 New peaks between 3000 and 3700 cm −1 are indicative of N−H stretching and sidechain stretching.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Upon heating above the lower critical solution temperature (LCST), the PNIPAM chains grafted on the particles undergo a typical reversible transition from water soluble hydrophilic coils to water insoluble hydrophobic globules [16][17][18]. This transition of the polymer transforms the silica surface into a surface with switchable properties, which is hydrophilic at normal (or room) temperatures and hydrophobic at elevated temperatures [19]. In addition, thermoresponsive polymers grafted on the surface of silica particles modify their packing behaviour and improve their stability [19].…”
Section: Introductionmentioning
confidence: 99%
“…This transition of the polymer transforms the silica surface into a surface with switchable properties, which is hydrophilic at normal (or room) temperatures and hydrophobic at elevated temperatures [19]. In addition, thermoresponsive polymers grafted on the surface of silica particles modify their packing behaviour and improve their stability [19]. In packed particle beds porosity is formed by the inter-particle voids.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, surface coating with a layer of sol-gel silica to construct core-shell structures has been used as a general method to improve the stability of the inner nanoparticles. [21][22][23][24][25][26][27][28] For example, Tong et al reported the use of poly(1-vinylimidazole)-graed Fe 3 O 4 @SiO 2 particles with improved stability as reusable adsorbents for the removal of Hg 2+ in waste water. 25 The protective ability of silica shells depends on their permeability to species that attack the inner nanoparticles.…”
Section: Introductionmentioning
confidence: 99%